Selected research on woody encroachment, glacial cross-valley profiles, and mass-movement disturbance regime landscapes - Weihs, Brandon Jeffery (Kansas State University, 2020)
This dissertation is a series of stand-alone journal articles and reports produced during my tenure as a Ph.D. student. All of these articles are peer-reviewed outside the Kansas State University system, and one of them is published in Papers in Applied Physical Geography, a peer-reviewed journal. The following dissertation is itemized by chapters that include these pieces; Woody encroachment of a riparian corridor in a tallgrass prairie: dendrochronological evidence from Kansas, USA; Slope Failures and Cross-valley Profiles, Grand Teton National Park, Wyoming; Mass-movement Disturbance Regime Landscapes, Hazards, and Water Implications: Grand Teton National Park, Wyoming.
Keywords: Parabolic glacial valleys; Mass movement; Geomorphology; Disturbance regime landscapes; Dendrochronology